THE EFFECT OF ASSET GROWTH, BUSINESS RISKS, AND INVESTMENT OPPORTUNITY SET (IOS) ON CAPITAL STRUCTURE AND COMPANY VALUE IN THE PROPERTY SECTOR AND REAL ESTATE COMPANIES LISTED ON THE IDX FOR THE 2017-2021 PERIOD - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan; Vol 4 No 4 (2024): LUCRUM : Jurnal Bisnis Terapan, 2025)
This study aimed to identify and analyze the effect of asset growth, business risk, and investment opportunity sets on capital structure and firm value. The population used in this study are property and real estate sector companies listed on the Indonesia Stock Exchange from 2017 to 2021, totaling 65 companies. Determination of the sample in this study using a purposive sampling technique so that the number of samples is as many as 34 companies. Data analysis uses path regression with the help of Smart PLS. The results of the research that has been carried out in this study are (1) Asset growth has a positive and insignificant effect on capital structure, (2) Business risk has a negative and significant effect on capital structure, (3) Investment opportunity set (IOS) has a negative and insignificant effect on capital structure, (4) capital structure has a positive and insignificant effect on firm value, (5) asset growth has a negative and significant effect on firm value, (6) business risk has a positive and insignificant effect on firm value to the firm and (7) Investment opportunity set (IOS) has a negative and insignificant effect on firm value.